2021
DOI: 10.3389/fnagi.2021.709998
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Neural Activity in Different Frequency Bands in Parkinson’s Disease With Mild Cognitive Impairment

Abstract: Background: Abnormal spontaneous neural activity is often found in patients with Parkinson’s disease with mild cognitive impairment (PD-MCI). However, the frequency dependence of neuronal interaction activities, especially the fractional amplitude of low-frequency fluctuation (fALFF) and degree centrality (DC), in PD-MCI is still unclear. Thus, this study aimed to explore the frequency dependence of PD-MCI based on fALFF and DC maps.Methods: Twenty-four patients with PD-MCI, 42 PD patients with normal cognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…MRI data acquisition and postprocessing were conducted as described previously (17). Briefly, a 3.0 T scanner with an 8-channel head coil (Signa Excite HD; GE Healthcare, Milwaukee, WI, USA) was used to collect MRI data.…”
Section: Magnetic Resonance Imaging (Mri) Data Acquisition and Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI data acquisition and postprocessing were conducted as described previously (17). Briefly, a 3.0 T scanner with an 8-channel head coil (Signa Excite HD; GE Healthcare, Milwaukee, WI, USA) was used to collect MRI data.…”
Section: Magnetic Resonance Imaging (Mri) Data Acquisition and Protocolmentioning
confidence: 99%
“…The participant recruitment process flowchart is displayed in Figure 1. The same sample of patients and controls were analyzed in our previous study from the perspective of fractional amplitude of lowfrequency fluctuation and degree centrality (17). The educational level of participants enrolled in this study was higher than primary school to control for the potentially confounding effect of years of education on cognitive assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Zuo et al ( 17 ) focused on the sub-frequency bands of the conventional frequency band and proposed the oscillations in the slow-4 (0.027–0.073 Hz) and slow-5 (0.01–0.027 Hz) bands, which mainly reflected gray matter signals and helped us to clarify the relationship between functional processing and disease. It is worth noting that many studies have indicated that the slow-4 and slow-5 frequency bands contribute differently to the conventional frequency oscillation ( 11 , 23 ), and frequency-dependent abnormalities exist in many disorders ( 7 , 11 ). For example, Yang et al ( 8 ) reported that abnormal amplitudes of Alzheimer’s disease were frequency-dependent, which were mainly related to the slow-5 band as opposed to than the slow-4 band.…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state functional magnetic resonance imaging (rs-fMRI) is a promising neuroimaging technique for exploring brain function, revealing the intrinsic spontaneous activity of the brain through the changes of magnetic resonance signaling generated by alterations in the blood oxygen level (10). It has been increasingly used to understand the neural mechanisms of various central nervous system diseases, such as depression, Parkinson's disease, and vascular cognitive impairment (7,11,12). Researchers have established various metrics to study resting-state functional data and to reflect the local and global characteristics of neural activity, which help us to understand spontaneous neural activity changes in the brain from different aspects (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…This graph-based measurement of network organization reflects the number of instantaneous functional connections between a region and the rest of the brain within the entire connectivity matrix of the brain (Guo et al, 2016). It has been widely used in neurological disorders, such as COPD, Parkinson's disease, Alzheimer's disease, and schizophrenia (Wang et al, 2019;Li et al, 2020;Rong et al, 2021). The DC approach was applied here to investigate altered brain functions after intervention in patients with COPD who received TCC rehabilitation practice.…”
Section: Introductionmentioning
confidence: 99%